5PSQ-120 Analysis of the pharmaceutical interventions performed on onco-haematological patients through an onco-haematology pharmacy consultation. Issue 1 (23rd March 2023) - Alarcon-Payer, C; Martín Roldan, A; Sánchez Suárez, MDM; Montero Vílchez, C; Jiménez Morales, A
Abstract : Background and Importance: In the area of onco-haematology, medication errors are of great importance because oral antineoplastic drugs have a narrow therapeutic margin, complex dosing regimens, possible interactions with other drugs and foods, and low supervision of their self-administration by healthcare professionals, increasing the risk of medication errors. Aim and Objectives: To analyse the pharmaceutical interventions performed on onco-haematology patients seen in an Onco-haematology Pharmacy consultation. Material and Methods: Prospective observational study of onco-haematology patients in a tertiary hospital for a period of one year. To identify the type of intervention performed, a database was created using an Excel ® spreadsheet to record and categorise it. Once identified, it was entered as an episode in the patient's clinical history in the Diraya Clinica ® programme so that the clinician could consult it in the patient's evolution. Finally, errors, interactions and adverse reactions avoided by performing these interventions were recorded. Results: A total of 35 onco-haematology patients underwent pharmaceutical interventions. 55% men and 45% women. The median age was 64 years. The patients belonged to two clinical services, 40.8% to Haematology and 59.2% to Oncology. The onco-haematological pathologies where most interventions were performed were: Prostate Cancer (30%), Colon Cancer (25%), Chronic Lymphatic Leukaemia (16%), Multiple Myeloma (10%), Ovarian Cancer (7%), Brain Tumours (5%), Lung Cancer (4%), Breast Cancer (3%). 45% of the pharmaceutical interventions performed were incorrect doses of antineoplastic drugs, 25% relevant drug interactions, 18% omission of the drug, 10% incorrect frequency of administration and 2% detected adverse reactions. The most frequent dose errors were poor adjustment for renal function (40%), failure to write the dose in the patient's clinical course (30%), failure to adjust for liver failure (20%), poor adjustment for body surface area (10%). 100% of the errors were detected in the pharmaceutical validation process during the dispensing of oral cytostatics. 100% of the pharmaceutical interventions were entered in the patient's clinical history as a clinical report. 97% were accepted and prevented 97% of medication errors in patients. Conclusion and Relevance: Pharmaceutical interventions have proven to be an effective tool to contribute to the achievement of the patient's therapeutic goals. References and/or Acknowledgements: 1. J Oncol Pract 2011;7(1): 7–12. Conflict of Interest: No conflict of interest.